Influência do fator neurotrófico derivado do cérebro (BDNF) na qualidade do sêmen de carneiros - Oliveira, Matheus Batista de (2024)
The group of proteins belonging to neurotrophins has been found to play a significant role in the development of reproductive tissues and exert an antioxidant action on spermatozoa. The present study aimed to assess the effect of the addition of different concentrations and exposure times to brain-derived neurotrophic factor (BDNF) on the semen quality of rams. One ejaculate from each Santa Inês ram (n=5) was collected using an artificial vagina, and only those with total motility values ≥ 70% (0 to 100%) and vigor ≥ 3 (0 to 5) were included. Semen samples from each ejaculate were subjected to different concentrations (0; 10; 20; 40; and 80 µg/L) and exposure times (T0 and T30 minutes) to BDNF. They were then analyzed for computer-assisted sperm analysis (CASA) and the percentage of spermatozoa with functional plasma membrane using the hypo-osmotic swelling test (HOST+), intact membrane (PMI+; SYBRGreen/Propidium Iodide), without oxidative stress (OS-; CellROX®), and with high mitochondrial membrane potential (MMP+; JC-1). Data normality was assessed using the Shapiro-Wilk test, and homoscedasticity was assessed using the Hartley test. The interaction effects between the five concentrations (Factor 1) and the two exposure times (Factor 2) to BDNF were studied. A mixed model (PROC MIXED) following a 5x2 factorial design was used, and the effects of the factors and their interactions were evaluated by the F-test. Differences between experimental groups were determined by the Tukey test. Data that did not show normal distribution were subjected to transformation by the arcsine square root. Even after transformation, those not normalized underwent non-parametric analyses using the Kruskal-Wallis test, followed by Dunn's post-hoc test. All evaluations were conducted considering a 95% confidence level (SAS®). BDNF concentration influenced semen quality, with 10 µg/L showing the highest percentages of spermatozoa with HOST+, PMI+, MMP+, and OE-. The exposure time also influenced semen quality, with T30 reducing the mean values of most kinetic parameters but not affecting HOST+, PMI+, MMP+, and OS-. The interaction between the concentration of 10 µg/L of BDNF and T30 increased the percentage of spermatozoa with functional plasma membrane compared to other interactions. It was concluded that the addition of BDNF at a concentration of 10 µg/L for 30 minutes improves the quality of ram semen.